Pengaruh Kematangan Karir terhadap Quarter Life Crisis pada Mahasiswa Psikologi Tingkat Akhir Universitas Negeri Padang - Sandani, Fidela Cahya; Rusli, Devi (Lembaga Yasin AlSys, 2024)
Final year students are currently experiencing a transition period from the academic world to the real world which is prone to experiencing a quarter life crisis. If students cannot deal with this situation well, it will have bad effects such as mild anxiety, panic attacks, and depression. One of the factors that influences the occurrence of a quarter life crisis is career maturity. Therefore, this research aims to find out whether maturity influences the quarter life crisis of final year psychology students at Padang State University. This research uses quantitative research methods with a correlational approach. The sampling technique used was a purposive technique and obtained 181 students who were active final year psychology students at Padang State University who were taking thesis or issues courses. This research uses measuring instruments in the form of a quarter life crisis scale from Fadhilah (2021), and a career maturity using a scale from Hamidah (2023). Data analysis uses simple regression test analysis techniques using the SPSS.26 program. The research results found that career maturity influenced the quarter life crisis in final year psychology students at Padang State University.